The Effect of Mergers on the Incentive to Invest in Cost Reducing Innovations - Robin Kleer (University of Würzburg, Department of Economics, 2006)
Both mergers and innovation are central elements of a firm's competitive strategy. However, model-theoretical analyses of the merger-innovation link is sparse. The aim of this paper is to analyze the impact of mergers on innovative activities and product market competition in the context of incremental process innovations. Inefficiencies due to organizational problems of mergers are accounted for. We show that optimal investment strategies depend on the resulting market structure and differ significantly from insider to outsider. In our linear model mergers turn out to increase social surplus.
Keywords: G34; O31; L22; L13; 330; Horizontal mergers; innovation; research joint venture; market structure